Hitler's first hundred days : when Germans embraced the Third Reich - Fritzsche, Peter 1959- (Basic Books, 2020)
"Over just a few months in spring 1933, Germany transformed from a deeply divided republic into a one-party Nazi dictatorship. In Hitler's First Hundred Days, award-winning historian Peter Fritzsche offers a probing new account of the dramatic and pivotal period when Germans became Nazis and the Third Reich began. Amid the ravages of economic depression, Germans in the early 1930s were pulled to political extremes both left and right. But after Adolf Hitler's appointment as chancellor in January, the Nazis moved with brutality and audaciousness to swiftly create a new political order. Fritzsche closely examines the events of these days--the elections and mass arrests, the gunfire and bonfires, the patriotic rallies and anti-Jewish boycotts--to understand both the terrifying power that the National Socialists exerted over ordinary Germans, and the powerful appeal of the new era they promised. Going down streets, up stairwells, and into German homes, rifling through newspapers,letters, and diaries, listening to the sounds of the radio and to song and slogan, Fritzsche unfolds the moments when suddenly dissenting voices went silent and almost everyone seemed to be a Nazi. It was a time characterized by both coercion and consent--but ultimately, a majority of Germans preferred the Nazi future to the Weimar past. Remarkably rich and illuminating, Hitler's First Hundred Days is the chilling story of the beginning of the end, when one hundred days seemed to inaugurate a new thousand-year Reich"--